EFFECT OF RICE STRAW BURNING ON SOIL TEMPERATURE REGIME - V. A. Ladatko; М. A. Ladatko (Зерновое хозяйство России, 2018)
In spite of the existing bans of rice straw burning, that have objective reasons (lack of technical means for mincing and plowing of straw) during the whole period of domestic production, this way of rice straw utilization remains the only possible one. However, the short-term and long-term consequences of the methods of removing of the grain part of the yield from the fields remain unsolved. The article has presented the data about the change of soil temperature regime during rice straw burning. The researches carried out in ‘Maryanskoe’ (Krasnoarmeysky region, Krasnodar Area) showed that burning of 8.2-9.3 tons of straw per ha increases soil temperature up to 590-630°С. The speed of temperature increase is of 470°С a minute, in some periods it is more than 50°С a second. The subsequent decrease of temperature runs more smoothly, after 130°С (in the period of smoldering ash) it decreases slower. However, even such high temperatures do not heat soil more than 25°С at the studied depths. Even in the upper layer of the soil (0-2 cm) the humus does not burn, and on the surface of the soil there is incompletely burnt debris of stalks, fine particles of straw and husk. Increase of the depth from the surface of soil the response to the temperature stress was more continuous, and the temperature increase itself was less noticeable. On the depth of 4,6,8 and 10 cm the maximum heat of the soil was 3.1-3.9, 2.0-2.2, 1.1-1.2 and 0.2-0.3°С respectively.